Random votes under compulsory voting: Evidence from Brazil. (August 2020) - Freire, Alessandro; Turgeon, Mathieu
Abstract: Compulsory voting is known for boosting electoral turnout, even when sanctions for abstaining are small or loosely enforced. Much less is known, however, about the consequences of compulsory voting on vote choice, and, in particular, about the quality of electoral decisions. In this paper, we explore the extent to which voters meaningfully engage in the electoral process or simply vote randomly because voting is required by law. We conducted a large online survey in Brazil during the 2018 national elections to assess if voters engage in random voting. We evaluate random voting for low-profile, low-information elected offices (state and federal legislators) and others that receive greater media coverage (governor and president) and evaluate the determinants of random voting for each of them. We find that: 1) random voting does not appear to be affected by social desirability bias; 2) there is substantial random voting under compulsory voting; 3) more voters tend to engage in random voting in low-profile, low-information elections, as compared to elections that receive greater media coverage; and, 4) interest in politics, education, and disposition to vote if voting were to be voluntary reduce random voting. Our findings carry important implications for the study of citizen participation and civic competence under compulsory voting and for democratic representation, more broadly.